Deaf to women: Rhodes's refusal to hear women or his own feminine voice within – a reading of Schreiner's Trooper Peter Halket of Mashonaland. Issue 1 (2nd January 2016) - Chetty, Rajendra; Curr, Matthew
ABSTRACT: E.D. Morel's chapter, 'The story of Southern Rhodesia', in his signal text The black man's burden (1920), provides intertextual reference to Olive Schreiner's work Trooper Peter Halket of Mashonaland (1897) in discussing libertarian thought and distinguishing aspects of male/female authorship . Schreiner's feminist perspective affords her a wider purview of colonialist prerogatives than those exhibited by several contemporary male observers or commentators. The figure of Jesus, as pictured in her neglected political/moral parable, far from being ironic, sentimental or evangelical in purpose, embodies her ideal balance of female and male qualities. Schreiner relies on this redemptive icon both in an ethical and gendered sense to project new understanding and enlightenment onto the strife of the day, which allows her, in turn, to expose and critique Rhodes's male deafness both to women and his own feminine nature. By contrast, Halket's conversion, his feminisation, holds up the alternative of hope versus Rhodes's predatory male soul and final moral damnation.